2001
DOI: 10.1079/bjn2001382
|View full text |Cite
|
Sign up to set email alerts
|

BMI does not accurately predict overweight in Asian Indians in northern India

Abstract: Asian Indians are at high risk for the development of atherosclerosis and related complications, possibly initiated by higher body fat (BF). The present study attempted to establish appropriate cut-off levels of the BMI for defining overweight, considering percentage BF in healthy Asian Indians in northern India as the standard. A total of 123 healthy volunteers (eighty-six males aged 18±75 years and thirty-seven females aged 20±69 years) participated in the study. Clinical examination and anthropometric measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
242
3
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(267 citation statements)
references
References 26 publications
17
242
3
5
Order By: Relevance
“…First, BMI does not reflect fatness uniformly in all populations and different ethnic groups 93941. The previous Omani study indicated that WHR and WC better predict CVD risk than BMI 3233.…”
Section: Discussionmentioning
confidence: 98%
“…First, BMI does not reflect fatness uniformly in all populations and different ethnic groups 93941. The previous Omani study indicated that WHR and WC better predict CVD risk than BMI 3233.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, most existing studies of SA have focused on Indians (8,14,17,18,(30)(31)(32) , neglecting other groups of SA. The present work represents one of only a few studies to examine MetS prevalence (and the prevalence of abnormal indicators) in the USA in a large sample of SA Americans of different ethnicities and use the newer suggested cut-offs.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropometric measurements (body mass index (BMI), waist circumference, waist-to-hip circumference ratio (W-HR), skinfold thickness at four sites (biceps, triceps, subscapular, and suprailiac), and sum of skinfolds ( P 4SF)) and percentage of body fat (%BF) were assessed as described previously. 17 An electrocardiogram was obtained in all the subjects.…”
Section: Patientsmentioning
confidence: 99%
“…24 Total skinfold thickness ( P 4SF) was defined as high when the value exceeded 50 mm. 17 Normolipidemia was defined by the standard criteria used by National Cholesterol Educational Program, Adult Treatment Panel III. 19 SPECT of the brain The subjects were injected Technetium-99m hexamethylpropylamine oxime ( 99m Tc-HMPAO) or Technetium-99m ethylene cysteine dimer ( 99m Tc-ECD) before the procedure.…”
Section: Biochemical Investigationsmentioning
confidence: 99%